2020
DOI: 10.7592/ejhr2020.8.2.kianbakht
|View full text |Cite
|
Sign up to set email alerts
|

Towards a comprehensive theory of culturally constructed humour

Abstract: In the present research, we discuss Humour Studies within Linguistics, focusing mainly on linguistic theories of humour including the Semantic Script Theory of Humour (SSTH; Raskin 1985), and the General Theory of Verbal Humour (GTVH; Attardo 1994, 2017b). The study demonstrates different types of cultural conceptualisations (Sharifian 2017a, 2017b) that the interlocutors draw upon, such as cultural categories, cultural metaphors, and cultural schemas to create humour, and we argue that the General Theory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Thus, Stankić (2017, p. 95) submits that ‘the production, perception and appreciation of humour are closely related not only to the individual dynamic meaning construction in the cognitive linguistic sense, but also cultural conceptualisations of a particular cultural group’. It is against this backdrop that Kianbakht (2020) contends that cultural conceptualisations should be considered in identifying and analysing instantiations of humour. Meanwhile, this study has significantly stimulated interesting discussions about food, language, culture and humour in the Nigerian environment, it also stimulates further studies to explore the semiotics of pictorial food metaphors in the Nigerian world as well as social media conceptualisations of fast food in Nigeria's food culture.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Stankić (2017, p. 95) submits that ‘the production, perception and appreciation of humour are closely related not only to the individual dynamic meaning construction in the cognitive linguistic sense, but also cultural conceptualisations of a particular cultural group’. It is against this backdrop that Kianbakht (2020) contends that cultural conceptualisations should be considered in identifying and analysing instantiations of humour. Meanwhile, this study has significantly stimulated interesting discussions about food, language, culture and humour in the Nigerian environment, it also stimulates further studies to explore the semiotics of pictorial food metaphors in the Nigerian world as well as social media conceptualisations of fast food in Nigeria's food culture.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some previous studies concluded that it is a rhetorical style lined with physical and mental health variables. As a rhetoric, humor is developed on the basis of local culture as it is closely related to norms and choice of language style of its speakers (Kianbakht, 2020). This concept was used in this study and the aspects of local culture, such as choice of Balinese language varieties and insertion of local culture was mapped in the study of Covid-19 humor discourses.…”
Section: Introductionmentioning
confidence: 99%
“…However, humour is especially interesting as an element of cultural heritage for its ability to accumulate, keep, and share knowledge and experience of many generations, to reflect cultural norms. As language and culture are interrelated, the language is one of the tools of keeping and transmitting cultural conceptualizations, emerging from the group-level cognition across time and space (Kianbakht, 2020). Thus, in the article special attention will be paid to the study of national and cultural specifics of humour in British and American political and economic programmes.…”
Section: Introductionmentioning
confidence: 99%